2014
DOI: 10.1007/s12032-014-0327-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of annexin A1 predicts poor prognosis in human hepatocellular carcinoma and enhances cell malignant phenotype

Abstract: Annexin A1 (ANXA1) belongs to the annexin superfamily of proteins, which contribute to the pathological consequence and sequelae of most serious human diseases. Recent studies have reported diverse roles of ANXA1 in various human cancers; however, its involvement in human hepatocellular carcinoma (HCC) still remains controversial. To investigate the expression pattern of ANXA1 in HCC tissues and evaluate its associations with tumor progression and patients' prognosis, immunohistochemistry was performed using 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
(27 reference statements)
2
35
0
Order By: Relevance
“…miR-26a regulated the proliferation and growth of cancer cells by targeting chromodomain helicase DNA binding protein 1 (35), growth regulation by estrogen in breast cancer 1 (35) and β-catenin (36). A number of studies demonstrated that the expression levels of miR-26a decreased in various types of tumor (23,37,38), whereas ANXA1 protein was overexpressed (39)(40)(41). Combined with the results of the present study suggesting that the miR-26a mimic may reduce the expression levels of ANXA1, a negative correlation was identified between miR-26a and ANXA1 in numerous tumors.…”
Section: Discussionsupporting
confidence: 78%
“…miR-26a regulated the proliferation and growth of cancer cells by targeting chromodomain helicase DNA binding protein 1 (35), growth regulation by estrogen in breast cancer 1 (35) and β-catenin (36). A number of studies demonstrated that the expression levels of miR-26a decreased in various types of tumor (23,37,38), whereas ANXA1 protein was overexpressed (39)(40)(41). Combined with the results of the present study suggesting that the miR-26a mimic may reduce the expression levels of ANXA1, a negative correlation was identified between miR-26a and ANXA1 in numerous tumors.…”
Section: Discussionsupporting
confidence: 78%
“…Previous reports suggest that ANXA1 is involved in membrane aggregation, cell matrix interaction, vesicle transport, phagocytosis, proliferation, apoptosis, inflammation and cell transformation29. ANXA1 expression is up-regulated in breast cancer30, hepatocellular carcinoma31, melanoma32, and rectal cancer, but down regulated in nasopharyngeal carcinoma33 and cervical cancer34. In breast cancer, ANXA1 expression is associated with BRCA1/2 mutations35.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, ANXA1 expression is associated with BRCA1/2 mutations35. Similarly, high ANXA1 expression correlated with advanced TNM stage and poor survival of human hepatocellular carcinoma (HCC) patients31. It has been shown that ANXA1 expressing cancer cells are resistant to chemo- and radiation therapy because these cells acquired cancer stem cell like features3637.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are differences in the understanding of the roles of ANXA1 in tumorigenesis. In some tumors, ANXA1 has been shown to stimulate cell proliferation and promote the invasion and metastasis of tumors (14,2124), whereas in other tumors, ANXA1 has been shown to exhibit the characteristics of a tumor suppressor gene, such as inhibiting cell proliferation and inducing apoptosis (11,2528). Thus, the expression of ANXA1 in malignant tumors seems to be tumor-specific, and plays multi-factorial roles.…”
Section: Discussionmentioning
confidence: 99%